The Implementation of TaRL Approach Assisted by E-Book Leveling Pelita as an Effort to Overcome Reading Literacy Vulnerability of Students of SDN Gisikdrono 02 Semarang - Panca Dewi Purwati; Nur Ummi Afifah; Dellia Fitria Kumara (Universitas Muhammadiyah Malang, 2025)
Implementing the Merdeka Curriculum provides learning services according to students' ability levels, and all students have the right to grade. This impacts the insecurity of reading literacy in advanced-class students. Students who have advanced to advanced classes (III, IV, V, and VI) find that not all students can read. Based on the results of the initial test at SDN Gisikdrono 2 from a total of 260 students, data obtained from 52 advanced class students (20%) who entered Phase A, students who could not read (27 people), and entered Phase B, not reading fluently (25 people). The purpose of this study is to describe the implementation of the TaRL approach assisted by Pelita leveling e-books and to describe the effectiveness of the TaRL approach assisted by Pelita leveling e-books in improving students' reading skills at both levels. This research was conducted using a mixed method. The data sources were students, pre-service PPL students, class teachers, and parents. The results of applying the TaRL approach assisted by the Pelita E-book can be described as follows. Both teams were given habituation and development literacy treatment with a schedule according to the agreement with parents and schools. Team A was given reading guidance using the Pelita Phase A E-book, and Team B was given reading guidance using the Pelita Phase B E-book. The handling of reading literacy insecurity was carried out for two months. It was found that the success rate of reading assessment (four indicators) reached 96.15% (50 students). Only two students could not read and were predicted to need special mentoring.